PEMBINAAN WAJIB PAJAK UMKM ORANG PRIBADI DALAM PELAKSANAN PP 23 TAHUN 2018 DI WILAYAH JAKARTA - Endro Andayani; Aji Prasetyo; Muhammad Yusuf (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
The socialization of PP 23 of 2018 which is an amendment to PP 46 of 2013 is very important to do because the socialization carried out by the government has not been carried out maximally so that still many UM KM Taxpayers (WP) have not clearly understood its implementation (Hendri, 2018). It is hoped that the guidance for UMKM Taxpayers (WP) whose turnover is less than 4.8 billion is expected to gain insight into what taxpayers can do related to the implementation of taxation and the responsibilities that must be carried out so that they are able to increase awareness to carry out their obligations which will then increase revenue. state revenue from the tax sector.This socialization was carried out through Community Service activities (PKM). In this PKM activity, Taxpayers (WP) are given PP 23/2018 material, insight into the rights and obligations of Taxpayers (WP), provide motivation for compliance in carrying out tax obligations and training on how to calculate, pay, and report taxes with the e billing system and e filling.The PKM results show an increase in knowledge about the implementation of PP 23/2018, new insights emerge that the procedures for calculating, paying and reporting taxes are carried out online so that it will simplify and speed up the process.The socialization of PP 23 of 2018 which is an amendment to PP 46 of 2013 is very important to do because the socialization carried out by the government has not been carried out maximally so that still many UM KM Taxpayers (WP) have not clearly understood its implementation (Hendri, 2018). It is hoped that the guidance for UMKM Taxpayers (WP) whose turnover is less than 4.8 billion is expected to gain insight into what taxpayers can do related to the implementation of taxation and the responsibilities that must be carried out so that they are able to increase awareness to carry out their obligations which will then increase revenue. state revenue from the tax sector.This socialization was carried out through Community Service activities (PKM). In this PKM activity, Taxpayers (WP) are given PP 23/2018 material, insight into the rights and obligations of Taxpayers (WP), provide motivation for compliance in carrying out tax obligations and training on how to calculate, pay, and report taxes with the e billing system and e filling.The PKM results show an increase in knowledge about the implementation of PP 23/2018, new insights emerge that the procedures for calculating, paying and reporting taxes are carried out online so that it will simplify and speed up the process